A new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from South India - Anbalagan, Sankarappan; Vijayan, Suruliyandi; Dinakaran, Sundaram; Krishnan, Muthukalingan (Zootaxa, 2019)
Simulium (Gomphostilbia) kumbakkaraiense sp. n. is described based on adults, pupae and mature larvae from Kumbakkarai stream, in the Palani Hills of Western Ghats, South India. This new species is placed in the Simulium batoense species-group of the subgenus Gomphostilbia Enderlein. This new species is characterized by a scutum with three brownish-black longitudinal vittae and hind basitarsus in the female 5.3 times as long as wide, and in male the large facets of the upper eye in 13 vertical columns and 14 horizontal rows, the respiratory gill with short common basal in the pupa and postgenal cleft arrow-head-shaped in the larva. Taxonomic notes are provided to distinguish this new species from related species. [Zoobank register: http://zoobank.org/urn:lsid:zoobank.org:act:C575FB25-B6B2-414B-AE11-0468A1871DFA]